STRATEGI PEMASARAN CV DIANA PHON BOGOR DENGAN PENDEKATAN STAKEHOLDER ENGAGEMENT STRATEGY - Tjedahwati, Rizal Syarief, dan Hartrisari Hardjomidjojo (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
CV Diana Phon Bogor is a small business in trading sector by selling various kinds of agricultural productssuch as pesticides, fertilizers, plant seeds, pots, and agricultural tools. Sales of CV Diana Phon Bogor in the last three years (2014-2016) have been decreased, it needs a new and right strategy to increase the sales. The purpose of this research was to design a marketing strategy for CV Diana Phon, Bogor. This research used the stakeholder engagement strategy method. Stakeholder engagement strategy sees involvement between stakeholders, in this case CV Diana Phon Bogor with suppliers and consumers. This research used descriptive approach that interviewed the owner and used questionnaire for suppliers and consumers. Stakeholder analysis results showed that 66.7% of suppliers were in engage category and 76.7% of consumers were in engage category. This showed that the stakeholders associated with CV Diana Phon Bogor were loyal. The design of marketing strategy undertaken was to maintain good relationships with stakeholders, in this case suppliers and consumers.Keyword: engagement, marketing, stakeholder, startegy